Comparação do efeito do plasma rico em plaquetas e fibrina rica em plaquetas no reparo do tendão de Aquiles em ratos - Dietrich, Franciele (2012)
OBJECTIVE : To evaluate and compare the effect of using Platelet-Rich Plasma (PRP) and Platelet-Rich Fibrin (PRF) in the repair of the Achilles tendon (TA) of rats. MATERIAL and METHODS : Forty-eight adult male rats randomized into three experimental groups: PRP, PRF and Control (saline 0.9%). A 3 cm longitudinal incision was made in the right leg of each rat in order to expose the TA. Later, it was a break in the same horizontal, and the repair performed with suture Kessler-type, when the sequence was applied 50 μL of the treatment in question. After 14 and 28 days postoperatively, the targeted part of the TA was removed, thus initializing the histological processing (Hematoxylin/Eosin; Sirius Red) to obtain results. The data obtained were expressed at 5% significance level (p <0.05) with mean ± SE. RESULTS : When comparing the three groups together, as to time and area of collagen type I and III, only statistical difference between the control group (16.22%) and the PRP group (37.16%) at 14 days after the treatment, no statistically significant difference was observed in the other groups. In the same way, when compared within groups of 14 and 28 days, the PRF group showed a significant difference for collagen I (27.76% and 47.74%) and III (66.94% and 46%) respectively. Control group showed significant difference in collagen type I (14.20% and 40.90%), not observed any significant difference in the PRP group. When evaluated on Hematoxylin/Eosin staining, PRP and control were similar in the times studied, differing only in the presence of hemorrhage, that was more expressed in the PRP group. Already the group PRF has shown to be more organized, especially in time of 28 days compared to the other two treatments. CONCLUSION : The data from this study suggest that the Platelet-Rich Fibrin tends to promote the accelerated regeneration of the Achilles tendon of rats, bringing promising prospects for future use in the clinic.